2012
DOI: 10.1161/circep.112.974436
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Ablation of the Pulmonary Veins and Cavo-Tricuspid Isthmus With a Magnetic Resonance Imaging–Compatible Externally Irrigated Ablation Catheter and Integrated Electrophysiology System

Abstract: Background— Magnetic resonance imaging (MRI)–guided interventional electrophysiology (EP) has rapidly emerged as a promising alternative to x-ray–guided ablation. We aimed to evaluate an externally irrigated MRI-compatible ablation catheter and integrated EP pacing and recording system, testing the feasibility of pulmonary vein and cavo-tricuspid isthmus ablation. Methods and Results— Externally irrigated MRI-compatible ablation and diagnostic EP cathet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 30 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, LGE imaging enables the assessment of additional arrhythmic substrates and postablation lesions within the left atrium (115). Recently, ablation procedures in an MR environment have become feasible in the research setting, potentially opening the door for radiation-free procedures in HCM patients (116,117).…”
Section: Role Of Mr Imaging In Atrial Fibrillation and Cardioembolic mentioning
confidence: 99%
“…Furthermore, LGE imaging enables the assessment of additional arrhythmic substrates and postablation lesions within the left atrium (115). Recently, ablation procedures in an MR environment have become feasible in the research setting, potentially opening the door for radiation-free procedures in HCM patients (116,117).…”
Section: Role Of Mr Imaging In Atrial Fibrillation and Cardioembolic mentioning
confidence: 99%
“…MR imaging-guided invasive diagnostic EP studies have been reported in animal studies and in a small series of five patients in which active and passive catheter-tracking techniques were used (12)(13)(14)(15)(16). We hypothesize that realtime MR imaging-guided radiofrequency ablation of atrial flutter is feasible in patients.…”
Section: Patient Populationmentioning
confidence: 96%
“…Using these systems, pre-clinical feasibility of electroanatomic mapping and ablation of the left ventricle [8], pulmonary veins and cavo-tricuspid isthmus [70, 71], and MR-guided cannulation of the coronary sinus [72] have been described. In recent years, electroanatomic mapping and ablation of atrial arrhythmias in humans have been reported [7375], which represents an important milestone in the clinical translation of iCMR (Fig.…”
Section: Icmr Applications Todaymentioning
confidence: 99%